On Compact Super Quasi-Einstein Warped Product with Nonpositive Scalar Curvature - Pahan, S.; Pal, B.; Bhattacharyya, A. (Журнал математической физики, анализа, геометрии, 2017)
This note deals with super quasi-Einstein warped product spaces. Here we establish that if M is a super quasi-Einstein warped product space with nonpositive scalar curvature and compact base, then M is simply a Riemannian product space. Next we give an example of super quasi-Einstein space-time. In the last section a warped product is defined on it.